THE IMPLEMENTATION OF SMART METHOD FOR IMPROVING JOB SATISFACTION - Tunnufus, Zakiyya; Rosyad, Sholeh; Moeins, Anoesyirwan (Dinasti Publisher, 2021)
The assessment of performance are subjective can have an impact on decreasing the job satisfaction of employees. when employees feel that they have worked well but based on the results of the assessment of their performance is not considered to provide optimum performance of them will feel disappointed. This study aims to evaluate the performance assessment by using the SMART method in PT. BNI Tbk. Main Branch Tangerang. The method used in this research is descriptive verificative, with a total sample of 98. Leverage data is done using kuesianer distributed to the employees of the bank PT. BNI Tbk. Main Branch Tangerang. The results showed that the performance assessment by using the SMART method can not be applied because some of the indicators SMART can not be implemented, while the job satisfaction provided by Bank BNI to the employee is still not optimal. The test results also indicate that performance assessment has positive and highly significant impact on job satisfaction of employees in the Bank PT. BNI Tbk. Main Branch Tangerang.